(untitled) (Seminar_BG, 2025)
In recent years, more and more authors have analyzed the role of digital media in politics by resorting to comparisons with feudalism. These authors come from different national contexts and from different disciplines such as anthropology, economics, political science, etc. This article attempts to initially systematize these comparisons with the feudal era by outlining two main approaches. The first approach introduces the concept of “platform feudalism” to describe the power relations between digital platforms (for communication or commerce) and their users. The second approach speaks of “technofeudalism” to describe the power relations between corporations, their users and the state. The first approach examines in depth the historical rise of new digital platforms, as well as the practices of their users and their consequences for the public sphere. The second approach examines the transition from platform power to infrastructure dominance of some platforms (AWS, Google and Microsoft) and follows the first chronologically because it analyzes precisely the more recent focus of these companies on the cloud as a service and as a key prerequisite for training Artificial Intelligence. After outlining these two fields of analysis, the article comments on how states respond to the power claims of technoplatforms in an attempt to protect (with greater or lesser success) their digital sovereignty. Attempts to find alternative solutions by states, however, are also not without problems, because the role of democratic participation in them is so far minimal. Thus, the digital transformations of our time and the new race to build a digital infrastructure on a global scale hang like a cloud over democracy. References: Baur, A. 2023. European Dreams of the Cloud: Imagining Innovation and Political Control. Geopolitics, 29(3), 796–820. Biesecker, M., Mednick, S., and Burke, G. 2025. As Israel uses US-made AI models in war, concerns arise about tech’s role in who lives and who dies. Associated Press. https://apnews.com/article/israel-palestinians-ai-technology-737bc17af7b03e98c29cec4e15d0f108. Blancato, F. G., & Carr, M. 2024. The trust deficit. EU bargaining for access and control over cloud infrastructures. Journal of European Public Policy, 1–32. Bria, F., Timmers, P., Gernone, F., Renda, A. , Fischer, C., Grabova, O. 2025. EuroStack – A European alternative for digital sovereignty. https://www.euro-stack.info/docs/EuroStack_2025.pdf Dichev, I. 2022. Platformen Feodalizam. Seminar_BG, 22. https://www.seminar-bg.eu/spisanie-seminar-bg/broy22/804-platformen-feodalizam.html. Dichev, I. 2010. Natsionalizmat kato subkultura. Seminar_BG, 4. https://www.seminar-bg.eu/spisanie-seminar-bg/broy4-tabloidnata-kultura/119-contents-broj4/486-natzionalizmat-kato-subkultura.html. Dichev, I. i Spasov, O. 2009. Novite mladi i novite medii. 2009. Institut Otvoreno obshtestvo, Sofia. Dichev, I. & Rone, J. (eds.). 2012. Novata kulturna geometria: uebmrezhovitsi, kulturbrakonieri, kiberagitatori. Sofia: Iztok-Zapad. Goldsmith, J. and Wu, T. 2006. Who Controls the Internet?: Illusions of a Borderless World. Oxford University Press. Gorwa, R. 2024. The Politics of Platform Regulation: How Governments Shape Online Content Moderation. Oxford University Press. Haggart, B. Iglesias Keller, C. 2021. Democratic legitimacy in global platform governance. Telecommunications Policy, ISSN 0308-5961, Elsevier, Amsterdam, 45(6). Haggart B, Schoolte JA, Tussikov N. 2021. Introduction: return of the state? In: Haggart B, Tuskov N, Scholte JA (eds) Power and Authority in Internet Governance Return of the State? London: Routledge, pp. 1–12. Hogan M .2015. Data flows and water woes: the Utah Data Center. Big Data & Society. Epub ahead of print 13 July. Kotliar, D. M., & Gekker, A. 2024. Migrating the state into corporate clouds. Information, Communication & Society, 27(14), 2566–2586. Lehdonvirta V. 2022. Cloud Empires: How Digital Platforms Are Overtaking the State and How We Can Regain Control. Cambridge, MA: MIT University Press. Libertson, F., Velkova, J., & Palm, J. 2021. Data-center infrastructure and energy gentrification: perspectives from Sweden. Sustainability: Science, Practice and Policy, 17(1), 152–161. Lyons, J. 2024. US government excoriates Microsoft for ’avoidable errors’ but keeps paying for its products. The Register. https://www.theregister.com/2024/04/05/microsoft_government_contracts/. Mineva. M. 2022. Kak se globalizira moralnata panika? Seminar_BG, 22. https://www.seminar-bg.eu/spisanie-seminar-bg/broy22/806-kak-se-globalizira-moralnata-panika.html. Morozov, E. 2022. Critique of Techno-Feudal Reason. New Left Review, 133-134. Nachtwey, O., & Seidl, T. 2023. The Solutionist Ethic and the Spirit of Digital Capitalism. Theory, Culture & Society, 41(2), 91-112. Open Future. 2023. Public Digital Infrastructure. https://openfuture.eu/wp-content/uploads/2024/07/240630infrastructure_consulation_response.pdf. Perry Barlow, J. 1996. A Declaration of the Independence of Cyberspace. Electronic Fronteer Foundation. https://www.eff.org/cyberspace-independence. Pollet, F. 2021. French decision to have Microsoft host Health Data Hub still attracts criticism. Euractiv. https://www.euractiv.com/section/health-consumers/news/french-decision-to-have-microsoft-host-health-data-hub-still-attracts-criticism/ Powers, S. and Jablonski, M. 2015. The Real Cyber War: The Political Economy of Internet Freedom. University of Illinois Press. Rone, J. 2023. The shape of the cloud: Contesting date centre construction in North Holland. New Media & Society, 26(10), 5999-6018. Rone, J. 2012. Culture wide closed: Pirate monopolies, forum dictatorship and nationalism in the practice of file sharing. In Media, Knowledge And Education: Cultures and Ethics of Sharing (Wolfgang Sützl, Felix Stalder, Ronald Maier and Theo Hug, eds.), Innsbruck University Press. Rosen, J.2011. Nie, horata, izvestni predi kato auditoriyata [ The People formerly known as the audience (Bulgarian translation)]. Seminar_BG, 6. https://www.seminar-bg.eu/spisanie-seminar-bg/broy6/122-contents-broj6/512-%D0%BD%D0%B8%D0%B5-%D1%85%D0%BE%D1%80%D0%B0%D1%82%D0%B0-%D0%B8%D0%B7%D0%B2%D0%B5%D1%81%D1%82%D0%BD%D0%B8-%D0%BF%D1%80%D0%B5%D0%B4%D0%B8-%D0%BA%D0%B0%D1%82%D0%BE-%D0%B0%D1%83%D0%B4%D0%B8%D1%82%D0%BE%D1%80%D0%B8%D1%8F%D1%82%D0%B0.html Speed, R. 2021. EU digital sovereignty project Gaia-X opens its summit with the departure of Scaleway. The Register. https://www.theregister.com/2021/11/19/scaleway_gaia_x/ Srivastava S. Corporate Sovereign Awakening and the Making of Modern State Sovereignty: New Archival Evidence from the English East India Company. International Organization. 2022;76(3):690-712. Treré, Emiliano. 2016. The Dark Side of Digital Politics: Understanding the Algorithmic Manufacturing of Consent and the Hindering of Online Dissidence. The Institute of Development Studies and Partner Organisations. Report. https://hdl.handle.net/20.500.12413/7697 Varoufakis, Y. 2023. Technofeudalism. What Killed Capitalism. London: Random House.